Institutional Ownership, Types of Industry, and Income Smoothing: Empirical Evidence from Indonesia - Eko Suyono (JAFFA, 2018)
This paper aims to evaluate the influence of institutional ownership and types of industry on income smoothing in the Indonesian listed firms. Basing on the literature and using panel data approach, it examines 112 firms listed on the Indonesia Stock Exchange during 2012 to 2016 periods  (i.e., 560 observations).  By using OLS regression to test the hypotheses, the result shows that institutional ownership does not influence significantly on income smoothing practice.  Moreover, types of industry do not influence on income smoothing practices, except for consumer goods industry which influences significantly on income smoothing practice.  With regard to the company size as a control variable, the result shows that company size influences positively on income smoothing practice.  Therefore, this study contributes in providing empirical evidence on the link between institutional ownership, types of industry, and income smoothing practice in emerging market context (i.e., Indonesia).